Synthesis and Characterization of Some Metal Complexes with their Sulfamethoxazoleand 4,4'-dimethyl-2,2'-bipyridyl and study Cytotoxic Effect on Hep-2 Cell Line (Baghdad Science Journal, 2015)
The ligand 4-amino-N-(5-methylisoxazole-3-yl)-benzene-sulfonamide(L1) (as a chelating ligand) was treated with Pd(II),Pt (IV) and Au(III) ions in alcoholic medium in order to prepare a series of new metal complexes. Mixed ligand complexes of this primary ligand were prepared in alcoholic medium in presence of the co-ligand 4,4'-dimethyl-2,2'-bipyridyl(L2) with Cu(II) ,Pd(II) and Au(III) ions. The complexes were characterized in solid state using flame atomic absorption, elemental analysis C.H.N.S, FT-IR, UV-Vis Spectroscopy, conductivity and magnetic susceptibility measurements. The nature of some complexes formed in ethanolic solution has been studied following the molar ratio method, also stability constant was studied and the complexes found to be stable in molar ratio1:1.an octahedral geometry was suggested for PdL1L2, PtL1and AuL1L2 complexes, square planar was suggested for AuL1 and PdL1complexes,while CuL1L2 complex has a square pyramidal geometry. Cytotoxic effect of theprepared complexes as well as ligands was evaluated against Hep-2 cell line using four different concentrations (625, 1250, 2500&5000 µg/ml) respectively in an exposure time 48 hrs comparing this effect with control positive Cis-Pt as reference drug. The obtained results refers to the higher inhibition rates of all complexes and their ligands and ligand (L1) and its complexes give more activity against tested cell than ligand (L2) and its complexes comparable with control positive .